Psychosocial problems of adolescent students of Hetauda municipality, Makwanpur, Nepal. - Bista, Bihungum (2013)
Executive Summary: Adolescence is the transitional stage of multi-faceted development, which ranges from 10-19 years. Among varieties of development aspect psychosocial development is crucial one and it is affected by different factors among them individual's own behavior, family and community environment are crucial. Nowadays, apart from those factors, school is also dominant factors. Imbalance in those factor lead to development to psychosocial problems. And this study aims to assess the prevalence of psychosocial problems in adolescent student and related factors. This cross sectional study was carried among 787 adolescent students in thirteen schools of Hetauda municipality with help of structured questionnaire and Y-PSC (Youth-Pediatric symptoms checklist) and stratified probability proportionate to size sampling technique was used to select students. Univariate, bivariate and multivariate analysis (Binary logistic regression) was functioned for assessing relationship different factors, at level of significance 0.05. Among total 787 adolescent students 134(17.03%) were suffering psychosocial problems. Male 74(9.50%) were more affected than female 60 (7.80%), furthermore it was increasing with age group and class. Multivariate analysis revealed age, existing problems, academic satisfaction and family related factors were significantly related with psychosocial problems. Among family factors, frequency of family dispute was highly associated with psychosocial problems (C.I of Odds Ratio= 2.27-77.23). Psychosocial problem among the adolescent was in alarming situation. More than individual demographic, behavioral, academic factors and family related factors were more responsible development of problem. So, for proper psychosocial development of adolescent student integrated effort from family to school level is responsible.